Cultural Meaning in Instrument Playing Technique Terms Karawitan Kendhang in Surakarta Style: Ethnolinguistic Study - Widayanti, Widayanti; Widodo, Widodo (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2025)
Based on the research results, it can be concluded that the technical terms for playing kendhang instruments in the Surakarta style musical can be grouped into two groups, namely monomorphemic and polymorphemic. There are 4 techniques in monomorphemic form, namely: tebok, kebug, keplak, penet. There are 4 polymorphemic techniques, namely: mbesut, njawil, tebokan bem, and tebokan kempyang. The cultural meaning of the technical terms for playing the Surakarta style kendhang karawitan instrument is that it describes the culture of the Javanese people in living their lives. The technical terms for playing the kendhang instrument do not only represent their sociocultural activism, but are also a symbol of the spiritual awareness of the Javanese people. This is because Javanese people have had an awareness since ancient times that humans are a small universe of all life.